The not-so-hidden partisan politics of community policing: Community police meetings in Buenos Aires, Argentina - MacColman, Leslie Elva (Theoretical criminology, 2023)
Community policing promises to foster collaboration between police and citizens, strengthen social cohesion, and address the root causes of crime and disorder. In order to understand why it often fails to achieve this, we argue that scholars should recognize community–police meetings as sites of dynamic, multi-scalar political contestation and pay closer attention to the not-so-hidden partisan struggles that shape them. Our empirical analysis focuses on Buenos Aires, Argentina. Based on ethnographic observation of 30 community–police meetings and interviews with 50 politicians, police officers, activists, and everyday citizens, we explain how higher-order partisan contests influenced the dynamics and outcomes of local meetings. We show how these meetings exacerbated social schisms, reified ideological differences between competing parties, and galvanized support for the City Government’s “law and order” policies. Our results suggest that local participation sometimes reinforces the punitive approaches to urban problems that community policing originally aimed to transcend.